Evolution in endoscopic endonasal approach for the management of hypothalamic–pituitary region metastasis: A single-institution experience - Baiano, Cinzia; Somma, Teresa; Franca, Raduan Ahmed; Di Costanzo, Marianna; Scala, Maria Rosaria; Cretella, Pasquale; Esposito, Felice; Cavallo, Luigi Maria; Cappabianca, Paolo; Solari, Domenico (Frontiers in Oncology, 2022)
Introduction Endonasal endoscopic surgery have changed the treatment perspectives for different lesions of the hypothalamic-pituitary region. The metastases of hypothalamus-pituitary region represent 0.4% of all intracranial metastatic tumors, and account for only 1.8% of surgically managed pituitary lesions. The aim of this study is to describe a single center institutional experience with 13 cases of hypothalamus-pituitary metastasis focused on presurgical workup, evolution of surgical technique, and post-surgical management according to our protocols for showing his effects on progression-free and overall survival rates for this relatively uncommon location. Material and methods We retrospectively reviewed the whole series of patients that received endoscopic endonasal approach at the Division of Neurosurgery at the University of Naples “Federico II” undergoing surgery from January 1997 to December 2021. We identified 13 cases whose pathology report revealed a metastatic lesion. Statistical analysis was performed to determine the Kaplan-Meier survival function and assess for log-rank differences in survival based on gender, surgical treatment, and post-operative therapy (p-value <0.02*). Results Pathology report disclosed lung adenocarcinoma (6 cases 46%), breast adenocarcinoma (2 cases; 15,4%) clear cell renal carcinoma (1 case, 7%), melanoma (7%) colorectal adenocarcinoma (1 case, 7%), uterine cervix carcinoma (7%), and follicular thyroid carcinoma (1 case, 7%). A standard endoscopic endonasal approach was performed in ten patients (76,9%), while the extended endonasal procedure in only three cases (23%). Biopsy was the surgical choice in 5 patients with infiltrative and invasive lesions and a poor performance status (38%), while, in cases where neurovascular decompression was necessary a subtotal resection was achieved in 5 patients (38%), a partial resection in 3 patients (23%). Median progression-free and overall survival were 14 and 18 months, (Table 3). There were statistically significant differences in PFS and OS in patients underwent adjuvant radiotherapy (p 0.019; p0.017 p-value 0.02). Conclusions The endoscopic endonasal approach is a viable approach for the management of hypothalamus-pituitary metastases as this surgery provides adequate opportunity of obtaining tissue sample and neurovascular decompression, both being crucial for continuing the integrated adjuvant therapy protocols.